MENINGKATKAN KECERDASAN KINESTETIK ANAK USIA DINI MELALUI MEDIA TARI MAPAG LAYUNG - Sobariah, Sobariah; Santana, Fifiet Dwi Tresna (IKIP Siliwangi, 2019)
The research aims to: 1). Knowing the objective conditions of children's kinesthetic intelligence intelligence before participating in the dance learning process. 2). Knowing the process of applying dance learning to improve children's kinesthetic intelligence 3). Knowing children's intelligence after dance learning is applied. This research carried out in this study is a qualitative research approach. The population of this research data is the students' children. The results of this study indicate that: 1). Early kinesthetic anxiety of children by teachers is relatively still using conventional methods in learning. Dance is only limited to sports and games that have to do with kinesthetic intelligence. 2). The process of learning steps for Mapag Layung Dance media is carried out through simple, not complicated implementation stages 3). Learning outcomes of Mapag Layung dance media in certain forms have contributed, such as in increasing kinesthetic anxiety in children in general, especially when starting to move the body and coordinating the arms of the feet and head with bending, it requires practice, concentration, creative thinking. Based on the results of the discussion that has been described, learning activities with the application of Mapag Layung Dance greatly impact the improvement of children's kinesthetic intelligence. The results of observations of children's motor improvement from before and after the Mapung Layung Dance showed optimal development.Penelitian bertujuan untuk: 1). Mengetahui kondisi objektif kecerdasan kecerdasan kinestetik anak-anak sebelum mengikuti proses pembelajaran tari. 2). Mengetahui proses penerapan pembelajaran tari untuk meningkatkan kecerdasan kinestetik anak 3). Mengetahui kecerdasan anak setelah diterapkan pembelajaran tari. Penelitian ini dilaksanakan dalam penelitian ini adalah pendekatan penelitian kualitatif. Populasi data penelitian ini adalah anak Siswa. Hasil penelitian ini menunjukan bahwa : 1). kecedasan kinestetik awal anak oleh guru relatif masih menggunakan metode konvensional dalam pembelajaran. Tarian hanya terbatas pada olah raga dan permainan yang ada kaitannya dengan dengan kecerdasan kinestetik. 2). Proses langkah-langkah pembelajaran media Tari Mapag Layung ditempuh melalui tahap-tahap pelaksanaan yang sederhana tidak rumit 3). Hasil Pembelajaran media Tari Mapag Layung dalam bentuk-bentuk tertentu telah memberikan kontribusi yang seperti dalam meningkatkan kecedasan kinestetik anak pada umumnya terutama bila mulai menggerakkan badan dan koordinasi tangan kaki dan kepala dengan lentur diperlukan latihan, konsentrasi, berpikir kreatif. Berdasarkan hasil pembahasan yang telah diuraikan, kegiatan pembelajaran dengan penerapan Tari Mapag Layung sangat berdampak terhadap peningkatkan kecerdasan kinestetik anak. Hasil observasi peningkatan motorik anak dari sebelum dan sesudah Tari Mapag Layung menunjukkan perkembangan yang optimal.